2001
DOI: 10.3354/cr018249
|View full text |Cite
|
Sign up to set email alerts
|

Phenological maps of Europe

Abstract: The geographical distribution of the timings of phenological phases is a precondition for detecting regional trends of the annual timings of phenological phases and finding their relationships to climate changes. Therefore phenological maps of Europe have been computed showing long-term means, trends and annual timings of extreme years. In this article maps of the beginning, the end and the length of the growing season as means over the years 1961-1998 as well as for the warm year 1990 are presented. Strong de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
118
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(135 citation statements)
references
References 6 publications
(10 reference statements)
14
118
1
2
Order By: Relevance
“…In this study, we found a 1.86 to 4.38 days delay in FBD per degree of latitude from south to north, which is consistent with Hopkins' law. Similar latitudinal patterns in spring phenophase were also found in Europe (Rötzer and Chmielewski 2001). Thus, strong dependences on latitude for spring plant phenophases exist in all continents of the Northern Hemisphere.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…In this study, we found a 1.86 to 4.38 days delay in FBD per degree of latitude from south to north, which is consistent with Hopkins' law. Similar latitudinal patterns in spring phenophase were also found in Europe (Rötzer and Chmielewski 2001). Thus, strong dependences on latitude for spring plant phenophases exist in all continents of the Northern Hemisphere.…”
Section: Discussionsupporting
confidence: 73%
“…In the western parts of the Table 3 Shift of temperature sensitivity of first bloom date (FBD) with latitude (a x ), longitude (a y ), and altitude (a z ) n number of phenological observation stations; the regression coefficients (a x , a y , a z ) and constant (c) of multiple regression model are shown. R 2 : goodness of fit; **P<0.01, *P<0.05 continents, the impact of longitude is significant in Europe, where the FBD delayed from the maritime regions in West Europe to the continental regions in East Europe (Rötzer and Chmielewski 2001). However, the impact of longitude on FBD is not obvious in the Western US (Table 2), which may be because the mountain range in the Western US blocked the warm maritime airflow (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations